ACTIVITY DETERMINATION OF PLANT EXTRACTS IN THE CONTROL OF CYANOBACTERIA. - JAWAD, ABDUL- LATEEF M. (Iraqi Journal of Aquaculture, 2022)
Some Iraqi plants which belonging to different families were extracted in 80% Ethanol and the ability of these extracts to control and growth of Cyanobacteria was evaluated. Results indicated that Artemisia campestris, Achillia santolina, Artemisia herba-alba and Centurea khotchii extracts were very active in inhibiting the growth of the test Cyanobacterial species. However, other plants extracts in this study did not show any promising algicidal potencies.